Method for improving pellet performance through cobalt smelting waste residues, obtained product and application
By mixing cobalt smelting waste slag with magnetite and bentonite and carrying out sphere making process, combined with hydrothermal modification and treatment, the problems of cobalt smelting waste slag storage pollution and resource utilization are solved, and the compressive strength of the pellet is significantly improved. Comprehensive performance realizes effective resource recycling and environmental protection of waste slag.
Patent Information
- Application Number
- CN202411342200.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The storage of cobalt smelting waste residue leads to environmental pollution and is difficult to effectively utilize the resource. The existing technology has shortcomings in resource recycling and waste residue utilization.
Mix the cobalt smelting waste slag with magnetite and bentonite, and make pellet ore through the pelletization process. Use the hydrothermal method to modify the cobalt smelting waste slag to improve its bonding performance. Add modified cobalt smelting to the pellet raw materials. Waste residue to enhance the compressive strength of the pellet.
The resource utilization of cobalt smelting waste slag has been achieved, which significantly improves the comprehensive performance of the pellet, including compressive strength and yield, meets the smelting needs of large blast furnaces, and reduces the pollution risk of waste slag.
Smart Images

Figure BDA0005060018110000081 
Figure BDA0005060018110000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metallurgical technology, and more specifically, relates to a method for improving pellet performance by utilizing cobalt smelting waste slag, and the obtained products and applications. Background Art
[0002] Cobalt concentrate is one of the main raw materials for hydrometallurgical cobalt smelting. In nature, cobalt concentrate is mainly produced as a co-product together with other minerals such as iron. Therefore, an important purification process in the hydrometallurgical cobalt smelting process is iron removal, which will produce a large amount of solid waste slag containing substances such as iron hydroxide, silicon dioxide, and calcium sulfate. At present, cobalt smelting waste slag is mainly treated by stockpiling or landfilling, which not only occupies precious land resources, but also leads to the loss of valuable metals. What is more serious is that the harmful substances in the long-term stockpiled cobalt smelting waste slag in the natural environment, such as sunlight, wind erosion, and rain erosion, may dissolve and penetrate into the soil and rivers, causing serious environmental pollution problems.
[0003] In order to better realize the comprehensive utilization of resources and environmental protection, researchers have been actively exploring ways to reuse waste slag. For example, by extracting valuable metals remaining in the waste slag to achieve resource recovery; or by solidifying the waste slag and using it in building materials, roadbed fillers, fired bricks, etc.
[0004] After searching, there are related patents published on the treatment of cobalt hydrometallurgical waste slag, such as the Chinese patent publication number CN111057837A, the publication date is January 26, 2020, and the patent name is a low-temperature roasting treatment method for cobalt hydrometallurgical waste slag. The patent obtains leached slag by low-temperature roasting, water leaching and pressure filtration, and controls the temperature and pH conditions to recover the valuable metals cobalt, nickel and copper, and at the same time forms ferrous sulfate heptahydrate as a by-product. Although this method can reduce the impact of waste slag storage on the environment to a certain extent, the process of wet extraction of valuable elements is complicated, the content of valuable elements in the waste slag is very low, and the extraction value is limited. At the same time, it will also produce new wastewater pollution, and the waste slag is not fully utilized.
[0005] For example, the Chinese patent publication number is CN111057837A, and the publication date is April 24, 2020. The patent name is a sintered brick based on cobalt smelting waste slag and its preparation method, which is made by mixing cobalt smelting waste slag, fly ash, and additives, pressing and molding after aging, and finally drying and calcining to obtain a sintered brick product. Although this method can achieve full quantitative utilization of waste slag, it does not realize resource utilization of valuable elements such as iron in the waste slag. Summary of the invention
[0006] 1. Problem to be solved
[0007] In view of the current problems of severe environmental pollution caused by the storage of cobalt smelting waste slag and great difficulty in effective resource utilization, the present invention provides a method for improving pellet performance by utilizing cobalt smelting waste slag. By adding cobalt smelting waste slag to pelletizing raw materials and utilizing the pelletizing process to realize resource utilization of cobalt smelting waste slag, it not only provides an effective way to digest the cobalt smelting waste slag, but also can significantly improve the comprehensive performance of the prepared pellets.
[0008] 2. Technical solution
[0009] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0010] The present invention provides a method for improving the performance of metallurgical pellets by utilizing cobalt smelting waste slag. The method comprises the following steps: uniformly mixing the cobalt smelting waste slag generated in the cobalt smelting industry with magnetite and bentonite, and then preparing a pellet product through a pelletizing process. The method can effectively solve the problem that the cobalt smelting waste slag is difficult to be recycled as a resource, and finally produce pellets with good performance indicators such as green ball falling and compressive strength, and roasted ball compressive strength, and also realize the volume reduction, harmlessness and resource utilization of the cobalt smelting waste slag.
[0011] Specifically, the above method comprises the following steps:
[0012] Step 1: Pretreatment of cobalt smelting waste slag;
[0013] The cobalt smelting waste slag is dried, crushed, ground and screened to obtain cobalt smelting waste slag particles, and a certain concentration of MgCl 2 The solution is used as a crystallizing agent to mix the cobalt smelting waste slag particles with MgCl 2 The solutions are mixed, and the suspension pH is adjusted by using a magnetic stirrer; the prepared cobalt smelting waste slag suspension is poured into a hydrothermal reactor, and the temperature is raised in an electric blast drying oven, and the reaction is carried out for a certain time after the temperature reaches the set reaction temperature; after the reactor is naturally cooled to room temperature, the product is opened and taken out, and the obtained product is immediately filtered and dried, and then crushed and sieved to obtain the modified cobalt smelting waste slag.
[0014] Step 2: adding water to magnetite powder, bentonite and modified cobalt smelting waste slag, mixing and pelletizing to form green balls;
[0015] Step 3, drying the raw balls;
[0016] Step 4: preheating and roasting the dried green balls to obtain roasted pellet products.
[0017] As a further preferred embodiment of the present invention, the cobalt smelting waste slag is dried and ground to ensure that the moisture content of the cobalt smelting waste slag is less than 1%, and the cobalt smelting waste slag particles with a particle size less than 0.074 mm are prepared, wherein the drying temperature is 90-120° C. and the drying time is 6-10 hours.
[0018] As the present invention is further preferred, in step one, cobalt smelting waste slag generates calcium sulfate whiskers by a hydrothermal method, and the calcium sulfate contained in the cobalt slag is prepared into calcium sulfate whiskers by carrying out the above-mentioned treatment on the cobalt smelting waste slag, and the calcium sulfate whiskers are hydrophilic materials, and the whiskers are slender, and the bonding effect is played in the pellets, and the reinforcing effect of the cobalt smelting waste slag on the performance of the pellets is further improved, and it can be ensured that the mixed cobalt smelting waste slag is fully combined with the magnetite powder. The pelletizing material of the present invention mainly selects magnetite, cobalt smelting waste slag and bentonite, wherein, magnetite is oxidized to hematite by magnetite during roasting, and in this process, due to the crystal transformation, the new hematite has a strong migration ability, and under high temperature roasting, the particles are connected by solid bonding to form a hematite crystal bridge, and the particles are connected, so that the pellets have a certain strength. The pellets of this strength can meet the use of small blast furnaces, but when used in large blast furnace scenes, it is still necessary to further improve its strength. Therefore, the present invention can not only effectively reduce the overall proportion of the pellet pore area by creatively adding modified cobalt smelting waste slag to the pellet raw material, but more importantly, after adding the cobalt smelting waste slag, the hematite grain size in the pellet can be enlarged, the connection is more dense, and the pores between the grains are significantly smaller. More optimally, after adding the modified cobalt smelting waste slag to the pellet raw material, the prepared pellets can obtain better compressive strength indicators.
[0019] As a further preferred embodiment of the present invention, MgCl 2 The solution is selected with a mass fraction of 1-3% MgCl 2 Solution, cobalt smelting waste particles and MgCl 2 The solid-liquid ratio of the solution was 1:15, and by adding Ca(OH) 2 The solution was adjusted to pH 8-9.
[0020] As a further preferred embodiment of the present invention, when preparing calcium sulfate whiskers, the reaction temperature is 120-150° C. and the reaction time is 1.5-3 h.
[0021] As a further preferred embodiment of the present invention, the particle size of the prepared modified cobalt smelting waste slag should be less than 0.074 mm.
[0022] As a further preferred embodiment of the present invention, in step 2, magnetite powder, bentonite and modified cobalt smelting waste slag are mixed according to the following mass parts: 94-98 parts of magnetite powder, 1-4 parts of bentonite, and 1-2 parts of cobalt smelting waste slag.
[0023] As a further preferred embodiment of the present invention, the added amount of the cobalt smelting waste slag accounts for 1-2% of the total pelletizing material mass. The present invention can effectively ensure the sulfur content in the prepared green balls by optimizing the design of the ratio of the cobalt smelting waste slag, and prevent the sulfur content in the green balls from being too high, which affects the compressive strength of the roasted pellets.
[0024] As a further preferred embodiment of the present invention, in step 2, the mass percentage content of the magnetite powder and bentonite in the -0.074 mm particle size is ≥ 98%. If the content is controlled within this range, the raw material particles have a large specific surface area and high balling performance.
[0025] As a further preferred embodiment of the present invention, in step 3, the green balls are dried by blast drying, and the specific drying process is: air temperature 280-320°C, blast flow rate 0.4-0.8m / s, blast time 5-10min;
[0026] In step 4, the preheating process: the preheating temperature is 900-1000°C, and the preheating time is 15-25 minutes; the roasting process: the roasting temperature is 1240-1300°C, and the roasting time is 15-30 minutes.
[0027] As a further preferred embodiment of the present invention, the cobalt smelting waste residue is industrial solid waste generated in the process of treating cobalt ore by the wet cobalt extraction industry, wherein Fe(OH) 3 ≥30% of cobalt smelting waste slag. Specifically, the cobalt smelting waste slag used in the present invention, after drying, mainly comprises the following components by mass: SiO 2 :25.16%,Fe(OH) 3 :33.65%, CaO: 13.92%, MnO: 0.65%, Al 2 O 3 :2.79%, MgO: 2.91%, TiO 2 : 1.22%, P 2 O 5 : 1.32%, S: 5.08%, Na: 5.03%, Cl: 2.83, Co: 0.84%, and the rest are unavoidable impurities;
[0028] The magnetite is a domestic concentrate powder, and its main components include the following components by mass: TFe: 64.77%, SiO 2 :2.07%, CaO: 0.78%, MgO: 0.72%, Al 2 O 3 : 1.09%, Na: 0.15%, and the rest are inevitable impurities.
[0029] The present invention also provides a roasted pellet product prepared by the method, the compressive strength of which is ≥3000N / piece.
[0030] The roasted pellet product of the present invention can be effectively used in a large blast furnace to produce molten iron.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention prepares pellets by adding cobalt smelting waste slag generated in the cobalt smelting industry to the raw materials for metallurgical pellet production, thereby effectively digesting the cobalt smelting waste slag during the metallurgical pellet preparation process. The strength of the pellets added with the cobalt smelting waste slag is between 3000 and 3600N, which meets the requirements of large-scale blast furnace smelting.
[0033] (2) The present invention prepares pellets by adding cobalt smelting waste slag to the pellet raw material, which can not only effectively solve the problem of resource utilization of cobalt smelting waste slag, but also further recover the valuable element iron in the cobalt smelting waste slag. At the same time, the Co element contained in the waste slag is reduced to a single substance and enters the molten iron. The Co element is a beneficial element in the steelmaking process of molten iron. Remaining in the molten steel can greatly improve the quality of steel, thereby realizing the resource utilization of cobalt smelting waste slag.
[0034] (3) The present invention uses a hydrothermal method to modify the added cobalt smelting waste slag, and prepares the calcium sulfate contained in the cobalt slag into calcium sulfate whiskers, which promotes the bonding effect of the pellets and further enhances the strengthening effect of the cobalt smelting waste slag on the performance of the pellets. It can ensure that the mixed cobalt smelting waste slag and magnetite powder are fully combined, so that the prepared pellets have better compressive strength indicators. DETAILED DESCRIPTION
[0035] The present invention discloses a method for improving the performance of metallurgical pellets by using cobalt smelting waste slag, which comprises drying, sieving, and modifying the cobalt smelting waste slag, and then adding the cobalt smelting waste slag to the pellet material for preparing the pellets, mixing the cobalt smelting waste slag with the pellet material, and then adding water to prepare the raw pellets, and then drying, preheating, and roasting the raw pellets to obtain roasted pellet products. The present invention not only effectively improves the comprehensive performance of the prepared pellets by adding modified cobalt smelting waste slag to the pellet material, especially significantly improves the compressive strength and yield rate of the roasted pellet products, but also realizes the volume reduction, harmlessness, and resource recovery of the cobalt smelting waste slag. Specifically, the method of the present invention comprises the following steps:
[0036] Step 1: Raw material preparation
[0037] (1) Pretreatment of cobalt smelting waste slag;
[0038] The cobalt smelting waste slag is dried at 90-120° C. for 6-10 hours, then crushed and ground, and sieved using a 0.074 mm pore size sieve to obtain cobalt smelting waste slag particles with a pore size of less than 0.074 mm.
[0039] (2) Modification of cobalt smelting waste slag
[0040] Prepare MgCl with a concentration of 1-3% 2 Solution, cobalt smelting waste particles and MgCl 2The solution was mixed and stirred thoroughly for 30 min with a magnetic stirrer, and (CaOH) was added dropwise to the suspension. 2 The solution is adjusted to a pH of 8 to 9; the prepared cobalt smelting waste slag suspension is poured into a hydrothermal reactor, and the temperature is raised in an electric blast drying oven to react at 120 to 150° C. for 1.5 to 3 hours; after the reactor is naturally cooled to room temperature, the product is taken out of the reactor, and the obtained product is immediately filtered, dried at 110° C. for 1 hour, and crushed and sieved to obtain modified cobalt smelting waste slag with a particle size of less than 0.074 mm.
[0041] (3) Magnetite powder and bentonite;
[0042] The magnetite powder and bentonite are subjected to particle size screening treatment to control the mass percentage content of the magnetite powder and bentonite to -0.074 mm particle size ≥ 98% for standby use.
[0043] Step 2: Raw ball preparation
[0044] 94-98 parts of magnetite powder, 1-4 parts of bentonite and 1-2 parts of modified cobalt smelting waste slag are fully mixed, then water is added to mix and ball-formed to form green balls. The moisture content of the prepared green balls is 8.0-9.0%.
[0045] It should be noted that the drop strength test of the green balls obtained above is carried out in the following specific steps:
[0046] Step S2.1, select 12 green balls of similar size, test one green ball at a time, and let it fall freely from a height of 0.5m onto a 10mm thick steel plate. Counting starts from 0 times, and repeat the drop test until cracks appear on the green ball, which is the number of drops. Calculate the average value as the green ball drop strength.
[0047] Step S2.2: Green ball compressive strength test
[0048] The green ball compressive strength test is carried out on the green ball compressive strength tester (YHKC 2A model) according to ISO 700 standard. Twelve green balls of similar size are selected, one green ball is tested each time, and the average value is calculated as the green ball compressive strength.
[0049] Step 3: Dry the raw balls
[0050] The qualified green balls are placed in a blast drying furnace at 280-320°C for drying. The blast flow rate is 0.4-0.8m / s, the blast time is 5-10min, and the number of green balls dried each time is 100.
[0051] Step 4: preheating and roasting the green balls to obtain roasted pellets
[0052] The dried green pellets are preheated in a tubular furnace at a temperature of 900-1000°C for 15-25 minutes; and then calcined in a tubular furnace at a temperature of 1240-1300°C for 15-30 minutes.
[0053] It should be noted that the compressive strength test of the calcined pellet product obtained above is carried out in the following specific steps:
[0054] Ten roasted pellets from the same batch were selected, and the crushing pressure of each pellet was measured using a JHY-5000 electronic universal pressure testing machine. The pressurization speed was maintained at 10 mm / min, and the average value was calculated after removing the extreme values to express the compressive strength, with the unit of "N / piece".
[0055] The present invention is further described below in conjunction with specific embodiments.
[0056] The pelletizing raw material components used in the following examples and comparative examples are as follows:
[0057] The dried cobalt smelting waste slag contains the following components by mass per 100 parts: SiO 2 :25.16 parts, Fe(OH) 3 : 33.65 parts, CaO: 13.92 parts, MnO: 0.65 parts, Al 2 O 3 : 2.79 parts, MgO: 2.91 parts, TiO 2 : 1.22 parts, P 2 O 5 : 1.32 parts, S: 5.08 parts, Na: 5.03 parts, Cl: 2.83 parts, Co: 0.84 parts, and the rest are unavoidable impurities;
[0058] Based on 100 parts, the magnetite includes the following components by mass: TFe: 64.77 parts, SiO 2 : 2.07 parts, CaO: 0.78 parts, MgO: 0.72 parts, Al 2 O 3 : 1.09 parts, Na: 0.15 parts, and the rest are inevitable impurities.
[0059] Based on 100 parts, the bentonite includes the following components in parts by mass: SO 2 : 70.36 parts, CaO: 2.74 parts, MgO: 2.47 parts, Al 2 O 3 : 18.03 parts, Na: 3.03 parts, TFe: 1.27 parts, and the rest are inevitable impurities.
[0060] Example 1
[0061] The method of manufacturing a roasted pellet product using cobalt smelting waste slag in this embodiment comprises the following steps:
[0062] Step 1: Raw material preparation
[0063] (1) Pretreatment of cobalt smelting waste slag;
[0064] The cobalt smelting waste slag was dried at 100° C. for 8 hours, and then crushed and ground, and sieved using a 0.074 mm pore size sieve to obtain cobalt smelting waste slag particles with a pore size less than 0.074 mm.
[0065] (2) Preparation of calcium sulfate whiskers
[0066] Prepare 2% MgCl 2 Solution, cobalt smelting waste particles and MgCl 2 The solution was mixed and stirred thoroughly for 30 min with a magnetic stirrer, and Ca(OH) 2 The solution was adjusted to a pH of 8.5; the prepared cobalt smelting waste slag suspension was poured into a hydrothermal reactor, and the temperature was raised in an electric blast drying oven, and the temperature was raised to 140° C. for 2 hours; after the reactor was naturally cooled to room temperature, the product was taken out of the reactor, and the obtained product was immediately filtered, dried at 110° C. for 1 hour, and crushed and sieved to obtain modified cobalt smelting waste slag with a particle size of less than 0.074 mm.
[0067] (3) Magnetite powder and bentonite;
[0068] The magnetite powder and bentonite are subjected to a grinding treatment to control the mass percentage content of the magnetite powder and bentonite at a particle size of -0.074 mm to be ≥98% for standby use.
[0069] Step 2: Raw ball preparation
[0070] Based on 100 parts, 96 parts of magnetite powder, 2 parts of bentonite and 2 parts of modified cobalt smelting waste slag are fully mixed, then water is added to mix and ball-formed to form green balls. The moisture content of the prepared green balls is 8.5%.
[0071] It should be noted that the drop strength test of the green balls obtained above is carried out in the following specific steps:
[0072] Step S2.1, select 12 green balls of similar size, test one green ball each time, and let it fall freely from a height of 0.5m onto a 10mm thick steel plate. Counting starts from 0 times, and repeat the drop test until cracks appear on the green ball, which is the number of drops. Calculate the average value as the green ball drop strength. The results are shown in Table 1.
[0073] Step S2.2: Green ball compressive strength test
[0074] The green ball compressive strength test was carried out on a green ball compressive strength tester (YHKC 2A) according to ISO 700. Twelve green balls of similar size were selected, one green ball was tested each time, and the average value was calculated as the green ball compressive strength. The results are shown in Table 1.
[0075] Step 3: Dry the raw balls
[0076] The qualified green balls are placed in a 300°C forced air drying furnace for drying. The air velocity is 0.6m / s, the air time is 8min, and the number of green balls dried each time is 100.
[0077] Step 4: preheating and roasting the green balls to obtain roasted pellets
[0078] The dried green pellets are preheated in a tubular furnace at a temperature of 950°C for 20 minutes; and then calcined in a tubular furnace at a temperature of 1250°C for 20 minutes.
[0079] It should be noted that the compressive strength test of the calcined pellet product obtained above is carried out in the following specific steps:
[0080] Ten roasted pellets from the same batch were selected, and the crushing pressure of each pellet was measured using a JHY-5000 electronic universal pressure testing machine. The pressurization speed was maintained at 10 mm / min, and the average value was calculated after removing the extreme values to express the compressive strength in "N / piece". The results are shown in Table 1.
[0081] Comparative Example 1
[0082] The method for preparing calcined pellets in this comparative example is different from that in Example 1 in that no cobalt smelting waste slag is added, and magnetite powder and bentonite (the amount of bentonite added is the same as in Example 1) are directly used as pelletizing raw materials to mix and form green balls. The pelletizing process operation and process parameters are the same as in Example 1. Then, the testing method of the present invention is used to test the drop strength and compressive strength of the prepared green balls. The results are shown in Table 1.
[0083] The same method as in Example 1 was used to dry, preheat and roast the green balls to obtain roasted pellet products, which were then tested for compressive strength. The results are shown in Table 1.
[0084] Comparative Example 2
[0085] The method for preparing calcined pellets in this comparative example is different from that in Example 1 in that an excessive amount of modified cobalt smelting waste slag is added to the pelletizing raw material, the modified cobalt smelting waste slag accounts for 3% of the total pelletizing material mass, and then mixed with bentonite (the amount of bentonite added is consistent with that in Example 1) to form green pellets. The pelletizing process operation and process parameters are the same as those in Example 1. Then, the drop strength and compressive strength of the prepared green pellets are tested by the testing method of the present invention. The results are shown in Table 1.
[0086] The same method as in Example 1 was used to dry, preheat and roast the green balls to obtain roasted pellet products, which were then tested for compressive strength. The results are shown in Table 1.
[0087] Comparative Example 3
[0088] The method for preparing calcined pellets in this comparative example is different from that in Example 1 in that the added cobalt smelting waste slag is not modified, and the dried cobalt smelting waste slag is directly mixed with magnetite powder and bentonite as pelletizing raw materials to form green pellets. The pelletizing process operation and process parameters are the same as those in Example 1. Then, the drop strength and compressive strength of the prepared green pellets are tested by the testing method of the present invention. The results are shown in Table 1.
[0089] The same method as in Example 1 was used to dry, preheat and roast the green balls to obtain roasted pellet products, which were then tested for compressive strength. The results are shown in Table 1.
[0090] Comparative Example 4
[0091] The method for preparing calcined pellets in this comparative example is different from that in Example 1 in that the added cobalt smelting waste slag is not pretreated, and the dried cobalt smelting waste slag is directly subjected to hydrothermal reaction to prepare calcium sulfate whiskers. The pelletizing process operation and process parameters are the same as those in Example 1. Then, the drop strength and compressive strength of the prepared raw balls are tested by the testing method of the present invention. The results are shown in Table 1.
[0092] The same method as in Example 1 was used to dry, preheat and roast the green balls to obtain roasted pellet products, which were then tested for compressive strength. The results are shown in Table 1.
[0093] Example 2
[0094] The method of this embodiment using cobalt smelting waste slag to produce a roasted pellet product has the same main steps as in embodiment 1, and the main difference from embodiment 1 is that the pelletizing raw material ratio is 97 parts of magnetite powder, 2 parts of bentonite and 1 part of modified cobalt smelting waste slag per 100 parts, which are fully mixed, and then water is added to mix and pelletize to form raw balls.
[0095] Example 3
[0096] The method of this embodiment of the present invention for producing roasted pellet products using cobalt smelting waste slag has the same main steps as those of the embodiment 1, and the main difference between the embodiment 1 and the embodiment 1 is that:
[0097] The drying process parameters of cobalt smelting waste slag are: drying temperature is 90℃, drying time is 10h;
[0098] The process parameters for modifying cobalt smelting waste slag are: using 1% concentration of MgCl 2 solution, the pH value of the reaction solution was adjusted to 8, the reaction temperature was 120°C, and the reaction time was 1.5h;
[0099] The drying process of green pellets is as follows: air temperature 320℃, air velocity 0.4m / s, and air time 10min;
[0100] Green ball preheating process: preheating temperature is 1000℃, preheating time is 15min;
[0101] Green ball roasting process: roasting temperature is 1300℃, roasting time is 15min.
[0102] Example 4
[0103] The method of this embodiment of the present invention for producing roasted pellet products using cobalt smelting waste slag has the same main steps as those of the embodiment 1, and the main difference between the embodiment 1 and the embodiment 1 is that:
[0104] The drying process parameters of cobalt smelting waste slag are: drying temperature is 120℃, drying time is 6h;
[0105] The process parameters for modifying cobalt smelting waste slag are: using 3% concentration of MgCl 2 solution, the pH value of the reaction solution was adjusted to 9, the reaction temperature was 150°C, and the reaction time was 3h;
[0106] The drying process of green pellets is as follows: air temperature 280℃, air velocity 0.8m / s, and air time 5min;
[0107] Green ball preheating process: preheating temperature is 900℃, preheating time is 25min;
[0108] Green ball roasting process: roasting temperature is 1240℃, roasting time is 30min.
[0109] The detection method of the present invention was used to detect the raw balls and roasted pellets obtained in the preparation process of Examples 2-4, and the detection results are shown in Table 1.
[0110] Table 1 Performance test results of green balls and roasted balls obtained in various embodiments and comparative examples of the present invention
[0111]
[0112] Combined with the data in Table 1, it can be seen that when the modified cobalt smelting waste slag is added to the pelletizing raw material for pelletizing, the comprehensive performance indicators of the pellets are greatly improved. When the addition amount of cobalt smelting waste slag is 1% and 2%, compared with the comparative example 1 without adding cobalt smelting waste slag, the compressive strength of the green balls and the compressive strength of the roasted pellets are significantly improved. Therefore, adding 1% to 2% by mass of modified cobalt smelting waste slag to the pelletizing material can significantly improve the comprehensive performance indicators of the oxidized pellets.
[0113] At the same time, in combination with Example 1 and Comparative Example 2, it can be seen that when the added modified cobalt smelting waste slag does not meet the scope of the present invention, although the compressive strength of the green ball is improved, the subsequent strength improvement of the roasted pellets is limited, and it is difficult to meet the use requirements of large blast furnaces.
[0114] In addition, the present invention also conducts a cobalt smelting waste slag pelletizing performance test, and the results are shown in Table 2. The results show that the cobalt smelting waste slag has good pelletizing performance, which fully explains the phenomenon that adding cobalt smelting waste slag to the pelletizing raw material improves the comprehensive performance indicators of the raw ball.
[0115] Table 2 Balling performance test results
[0116] type Maximum capillary water Largest molecule water Balling index[Note 1] Spherical evaluation magnetite 15.7 7.2 0.54 medium Cobalt smelting waste 64.84 41.96 1.81 excellent
[0117] Note 1: The static ball-forming index of a material refers to the ability of mineral powder to form balls when dripping water in a natural state. It is also a parameter for comprehensively evaluating the ball-forming performance of a material. It can reflect the specific surface area and hydrophilicity of the material and other various properties. K is usually used to represent the ball-forming performance of the material. It can reflect the specific surface area and hydrophilicity of the material and other various properties. K is usually used to represent the ball-forming performance of the material. Its value can be calculated by formula 1:
[0118]
[0119] Where: W 分 —Maximum molecular water, %; W 毛 —Maximum capillary water, %.
[0120] In summary, the present invention modifies the cobalt smelting waste slag produced during the cobalt smelting process and adds it to the pelletizing raw material to make pellets, which are added to the subsequent blast furnace process. The present invention uses the existing industrial process to treat the cobalt smelting waste slag, and prepares pellets after modifying it. The process is simple and easy to operate. It not only solves the problem of environmental pollution caused by cobalt smelting waste slag, but also improves the performance indicators of pellets, which plays a positive role in the existing process. The present invention has mature technology, no secondary pollution, small investment and low cost.
[0121] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.
[0122] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definition in this specification sheet shall prevail. When rate, pressure, temperature, time or other values or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.
Claims
1. A method for improving the performance of metallurgical pellets using cobalt smelting waste slag, characterized in that: The following steps are involved: Step 1: modifying the cobalt smelting waste slag to prepare modified cobalt smelting waste slag containing calcium sulfate whiskers; Step 2: adding water to magnetite powder, bentonite and modified cobalt smelting waste slag, mixing and pelletizing to form green balls; Step 3: Dry the raw balls; Step 4: preheating and roasting the dried green balls to obtain roasted pellet products.
2. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to claim 1, characterized in that: In step 1, the cobalt smelting waste slag is dried and ground to ensure that the moisture content of the cobalt smelting waste slag is less than 1%, and the cobalt smelting waste slag particles with a particle size of less than 0.074 mm are prepared.
3. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to claim 2, characterized in that: Drying process parameters: drying temperature is 90-120℃, and drying time is 6-10h.
4. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to claim 1, characterized in that: In step 1, the cobalt smelting waste slag particles are modified by a hydrothermal method. Specifically, the cobalt smelting waste slag particles and a MgCl2 solution are mixed and reacted, the pH of the reaction solution is adjusted to 8-9, the reaction temperature is 120-150°C, and the reaction time is 1.5-3h.
5. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to claim 4, characterized in that: In step 2, magnetite powder, bentonite and cobalt smelting waste slag are mixed according to the following mass parts: 94-98 parts of magnetite powder, 1-4 parts of bentonite, and 1-2 parts of cobalt smelting waste slag.
6. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to claim 5, characterized in that: The added amount of the cobalt smelting waste slag accounts for 1-2% of the total pelletizing material mass.
7. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to claim 5, characterized in that: In step 2, the magnetite powder and bentonite are both controlled to have a particle size of -0.074 mm, accounting for more than 98%.
8. The method for improving the performance of metallurgical pellets by using cobalt smelting waste slag according to any one of claims 1 to 7, characterized in that: In step 3, the green balls are dried by blast drying, and the specific drying process is: air temperature 280-320°C, blast flow rate 0.4-0.8m / s, blast time 5-10min; In step 4, preheating process: preheating temperature is 900-1000°C, and preheating time is 15-25min; Roasting Process: The roasting temperature is 1240-1300°C and the roasting time is 15-30 minutes.
9. A roasted pellet product, characterized in that: The pellets are prepared by the method for improving the performance of metallurgical pellets by using cobalt smelting waste slag as described in any one of claims 1 to 8, and the compressive strength of the roasted pellet product is ≥3000N / piece.
10. The use of the roasted pellet product according to claim 9, characterized in that: It is used as iron-making raw material and put into the blast furnace to produce molten iron.
Citation Information
Patent Citations
Low-temperature roasting treatment method for cobalt hydrometallurgy waste residues
CN111057837A
